2018
DOI: 10.2147/idr.s186994
|View full text |Cite
|
Sign up to set email alerts
|

Endemic dissemination of different sequence types of carbapenem-resistant <em>Klebsiella pneumoniae</em> strains harboring <em>bla</em><sub>NDM</sub> and <em>16S</em> <em>rRNA methylase</em> genes in Kerman hospitals, Iran, from 2015 to 2017

Abstract: IntroductionThe emergence and spread of Klebsiella pneumoniae strains resistant to multiple antimicrobial agents are considered as a serious challenge for nosocomial infections.Materials and methodsIn this study, 175 nonrepetitive clinical isolates of K. pneumoniae were collected from hospitalized patients in Kerman, Iran. Extended-spectrum β-lactamases (ESBLs), AmpC, and carbapenemase-producing isolates were recognized by phenotypic methods. The resistance genes including efflux pumps oqxA/oqxB, 16S rRNA meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…In the current study, ST392 has detected among NDM positive isolates with different ERIC patterns. Another detected ST, ST147 which is an international clone, has been reported from center, south and south east of Iran [6][7][8]. In our study, ST147 has been associated with CTX-M-G1, bla SHV-, aac6Ib-cr and armA.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the current study, ST392 has detected among NDM positive isolates with different ERIC patterns. Another detected ST, ST147 which is an international clone, has been reported from center, south and south east of Iran [6][7][8]. In our study, ST147 has been associated with CTX-M-G1, bla SHV-, aac6Ib-cr and armA.…”
Section: Discussionsupporting
confidence: 58%
“…Iran, as one of the Middle East countries, neighbor countries where the NDM and OXA-48 producing bacteria are endemic [6]. While bla NDM producing K. pneumoniae isolates have been reported from different cities of Iran in recent years, sequence types of these isolates are determined and published from three cities located in the center, south, and south-east of this country [6][7][8]. In our previous study, we reported a relatively high prevalence of bla OXA-48 /bla NDM-1 producing Enterobacteriaceae isolates collected from the large tertiary hospital of Semnan [9], an important city along the historical Silk Road.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a high rate of imipenem resistance in K. pneumoniae was reported from Iran [29,30]. Our previous studies demonstrated that New Delhi Metallo-beta lactamase (NDM) is responsible for carbapenem resistance in K. pneumoniae in Kerman, Iran [31,32]. Although the prevalence of imipenem-resistant hvKP strains in our study was low, the enhanced virulence of these strains and the possibility of acquiring antimicrobial resistance are a cause for concern.…”
Section: P R O V I S I O N a L P R O V I S I O N A Lmentioning
confidence: 47%
“…Polymerase chain reaction (PCR) was performed to detect carbapenemase genes (bla KPC , bla NDM , bla GIM , bla SPM , bla IMP , bla SIM , bla VIM , bla IMI and bla OXA-48-like ) in the CRKP strains and ESBLs genes (bla TEM , bla SHV , bla CTX-M-group , bla OXA-1-like , bla CTX-M-1-group, bla CTX-M-2group , bla CTX-M-9-group ) in the ESBL-producing strains [17,[19][20][21][22]. The commercial kits Green Taq Mix (Vazyme, Nanjing, China) and specific primers were used to detect resistance genes.…”
Section: Detection Of Resistance Genesmentioning
confidence: 99%